Improved Handover Routing Scheme In Hierarchical Mobile Ipv6 Networks - Vivaldi, Indra (2003)
Mobile Internet Protocol version 6 (MIPv6) has been proposed to solve the problem of mobility in the new era of Internet. MIPv6 is a proposal for handling routing of IPv6 packets to mobile nodes that have moved away from their home network. In the near future, with the simultaneous growth of the mobile user population and the Internet, users will move more frequently between networks as they stay connected to the Internet and access its resources. Thus, as mobility increases across networks, handovers will significantly give impact on the quality of the connection and on user application . Previous research has shown that MIPv6 only defines a means of managing global mobility (macro-mobility) but does not address local mobility (micro-mobility) separately. Instead, it uses the same mechanism in both cases. This involves long handover delay and a lot of signaling. The extension of protocol of basic MIPv6 has been investigated. Internet Engineering Task Force (IETF) introduced Hierarchical Mobile IPv6 (HMIPv6) . HMIPv6 is the proposed enhancement of MIPv6 that is designed to reduce the amount of signaling required and to improve handover speed for mobile connections. New node in HMIPv6 called the mobility anchor point (MAP) serves as a local entity to aid in mobile handover. By separating global and local mobility, HMIPv6 makes it possible to deal with either situation of macro mobility and micro mobility appropriately. The MAP helps to decrease the delay and packet loss during handover. HMIPv6's handover operation has been investigated. We have analyzed the handover routing scheme on Internet Protocol (IP) layer. The operation of this handover starts from the mobile node (MN) sends binding update (BU) to its new network until MN receives packet from the correspondent node (CN) or home agent (HA) through its new network. The adoption of multicast scheme and the avoidance of redundancy in sending binding update scheme have been proposed and have been implemented to HMIPv6. Proposed multicast scheme may allow MN to receive packets during handover operation. The avoidance of redundancy in sending B U scheme may reduce the amount of signaling for the handover thus reduce the handover delay. We have tested the performance of HMIPv6 with the proposed schemes based on simulation study. The results show that our proposed schemes reduce the handover delay and the amount of packet loss in HMIPv6.